Experimental and analytical study on load paths of RC squat walls with openings - Qian, Kai (2017)
Two series of experimental tests on reinforced concrete (RC) squat walls with irregular openings were analysed. The experimental evidence indicated that flanges significantly affect the failure modes, initial stiffness, ultimate strength and deformation capacity. Given the complexity of the stress distribution in walls with irregular openings, strut-and-tie models are generally used in design and analysis to explicitly demonstrate the shear force transfer and load distribution paths. A comparison of experimental data with analytical results from the existing strut-and-tie model indicated that the latter may underestimate the ultimate strength by 51%. Although the strut-and-tie model is a lower-bound solution, the underestimation of 51% is still very large and may lead to unfavourable shear failure. An improved strut-and-tie model was thus developed, based on test observations. The improved strut-and-tie model can provide a more accurate prediction for the ultimate strength of walls with irregular openings. Based on the model, design recommendations and suggestions for reinforcement details in RC walls with irregular openings are also presented.